A forty-year review of Rocky Mountain spotted fever cases in California shows clinical and epidemiologic changes. - Anne M Kjemtrup; Kerry Padgett; Christopher D Paddock; Sharon Messenger; Jill K Hacker; Tina Feiszli; Michael Melgar; Marco E Metzger; Renjie Hu; Vicki L Kramer (Public Library of Science (PLoS), 2022)
Rocky Mountain spotted fever (RMSF) is a life-threatening tick-borne disease documented in North, Central, and South America. In California, RMSF is rare; nonetheless, recent fatal cases highlight ecological cycles of the two genera of ticks, Dermacentor and Rhipicephalus, known to transmit the disease. These ticks occur in completely different habitats (sylvatic and peridomestic, respectively) resulting in different exposure risks for humans. This study summarizes the demographic, exposure, and clinical aspects associated with the last 40 years of reported RMSF cases to the California Department of Public Health (CDPH). Seventy-eight RMSF cases with onsets from 1980 to 2019 were reviewed. The incidence of RMSF has risen in the last 20 years from 0.04 cases per million to 0.07 cases per million (a two-fold increase in reports), though the percentage of cases that were confirmed dropped significantly from 72% to 25% of all reported cases. Notably, Hispanic/Latino populations saw the greatest rise in incidence. Cases of RMSF in California result from autochthonous and out-of-state exposures. During the last 20 years, more cases reported exposure in Southern California or Mexico than in the previous 20 years. The driver of these epidemiologic changes is likely the establishment and expansion of Rhipicephalus sanguineus sensu lato ticks in Southern California and on-going outbreaks of RMSF in northern Mexico. Analysis of available electronically reported clinical data from 2011 to 2019 showed that 57% of reported cases presented with serious illness requiring hospitalization with a 7% mortality. The difficulty in recognizing RMSF is due to a non-specific clinical presentation; however, querying patients on the potential of tick exposure in both sylvatic and peridomestic environments may facilitate appropriate testing and treatment.